2013
DOI: 10.1177/1934578x1300800901
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Biosynthesis of Valerenadiene and Related Sesquiterpenes

Abstract: It is proposed that the biosynthesis of the sesquiterpene valerenadiene, a key intermediate in the biosynthesis of a sedative in valerian, involves cyclopropane and not cyclobutane intermediates and includes as a key step a cyclopropylcarbinylcation-cyclopropylcarbinylcation rearrangement analogous to the one observed in the conversion of presqualene to squalene in triterpene and steroid biosynthesis. Similar mechanisms are proposed for the biosynthesis of the related sesquiterpenes pacifigorgiol, tamariscene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Proposed Catalytic Cascades for the Sesquiterpene Reaction Products Generated by VDS and VDS Mutants a a Valerena-1,10-diene (17) is the predominate reaction product of the wild type VDS and can arise from two possible routes, initiated by either a 1,10 (germacrenyl route, red arrows and highlighting) or a 1,11 (humulyl route, blue arrows and highlighting) ring closure of 1. 16,17,48 The other major products, 9 and 10, generated by wild type VDS, could arise from a germacrenyl cation route as suggested previously. 62,67 An earlier study also used specifically labeled FPP to suggest the biosynthetic origin of α-gurjunene (12) via a germacrenyl route.…”
Section: ■ Materials and Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…Proposed Catalytic Cascades for the Sesquiterpene Reaction Products Generated by VDS and VDS Mutants a a Valerena-1,10-diene (17) is the predominate reaction product of the wild type VDS and can arise from two possible routes, initiated by either a 1,10 (germacrenyl route, red arrows and highlighting) or a 1,11 (humulyl route, blue arrows and highlighting) ring closure of 1. 16,17,48 The other major products, 9 and 10, generated by wild type VDS, could arise from a germacrenyl cation route as suggested previously. 62,67 An earlier study also used specifically labeled FPP to suggest the biosynthetic origin of α-gurjunene (12) via a germacrenyl route.…”
Section: ■ Materials and Methodsmentioning
confidence: 64%
“…This is subsequently followed by concomitant deprotonation at C1 of the germacrenyl cation intermediate ( 3) leading to the formation of the C1−C11 bond and yielding the bicyclo- germacrene ( 9) intermediate (Scheme 1). 57 According to the mechanistic model of Paknikar et al, 48 17 can form from the bicyclogermacrene intermediate via an energetically unfavorable cyclopropylcarbinyl cation rearrangement (CCR), a mechanism utilized by eukaryotes in the biosynthesis of triterpenoids that is useful in medicinal and industrial applications. 58−61 This model is also consistent with the 13 C labeling studies of Yeo et al 17 Altogether, VDS appears to be a promiscuous enzyme that generates multiple reaction products, a precedent reported for many other terpene synthases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few other feasible mechanisms for the formation of follower 3 could be devised, and only the one presented fits the observation of 13C enriched label at the C-3′ position of follower 3. Hence the key rearrangement is cyclopropylcarbinyl cation-cyclopropylcarbinyl cation rearrangement (CCR) [3,4]. During the deuteriation of commercial acetyl cedrene, the follower was also deuterated, and it was observed that aromatic protons are exchanged.…”
Section: Terpenes and Terpenoidsmentioning
confidence: 99%
“…Based on the experimental labeling data of Pyle et al [30] and Yeo et al [31], Paknikar et al [4] proposed a new alternate biosynthetic route (Scheme 19) from IPP to valerenadiene 47 which fits the unusual 13C labeling found in valerian and avoids the previously unreported triene 54.…”
Section: Biosynthesis Of Valerenadienementioning
confidence: 99%